Analisis Harga Pokok Produksi Kelapa Sawit di Afdeling I Kebun Bangun PT Perkebunan Nusantara IV Regional I - Dio Alfareza Alfatwa; Febriana Roosmawati; Tuty Ningsih; Adi Widjajanto (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Cost of good sold is a crucial element in a cost accounting system that reflects the total sacrifice of resources to produce a product. This cost of goods sold will determine the amount of profit that will be generated in a production process so that in principle, companies that produce in bulk collect their production costs using the process cost method. Bangun Plantation as part of Region I PTPN IV has its own characteristics and challenges in managing palm oil production. However, there are not many studies that specifically examine the cost structure and calculation of cost of good sold in this plantation. This study aims to determine the amount of the cost of production of oil palm fruit bunches in Bangun Plantation. The research method used is quantitative descriptive research. Based on the research findings, the production cost structure for 2024 at Afdeling I of the Bangun Estate (PT Perkebunan Nusantara III) is as follows: salaries and allowances for management-level employees (3%), maintenance of productive crops (10%), fertilization (32%), harvesting (21%), transport to the mill (10%), overhead costs (16%), and overhead depreciation costs (8%). According to the Work Plan and Budget (RKAP), the average cost of production for the Bangun Estate is Rp 1,020/kg in 2024, with an average production cost of Rp 26,333,838/ha and a production volume of 26.22 tons/ha. The cost of production (HPP) for fresh fruit bunches at the Bangun Estate was Rp 510/kg in 2020, Rp 809/kg in 2021, Rp 963/kg in 2022, Rp 1,545/kg in 2023, and Rp 1,469/kg in 2024.